2021
DOI: 10.3389/fpls.2021.741050
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Turnip Mosaic Virus Infections on the Deposition of Secondary Cell Walls and Developmental Defects in Arabidopsis Plants Are Virus-Strain Specific

Abstract: Two isolates of Turnip mosaic virus (UK 1 and JPN 1), representative of two different viral strains, induced differential alterations on secondary cell wall (SCW) development in Arabidopsis thaliana, suggesting cell-type specific effects of these viral infections. These potential effects were analyzed in inflorescence stems and flowers of infected plants, together with other possible cellular effects of the infections. Results obtained from macroscopic and histochemical analyses showed that infection with eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…We hypothesize that the loosening of cell walls on these hosts may facilitate the deformation of plasmodesmata and enable the faster spread of the virus from one cell to another and, ultimately, to the entire host via the phloem. In line with our results, López-González et al . (2021) showed that TuMV-infected plants downregulate genes related with the formation of the secondary cell wall.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We hypothesize that the loosening of cell walls on these hosts may facilitate the deformation of plasmodesmata and enable the faster spread of the virus from one cell to another and, ultimately, to the entire host via the phloem. In line with our results, López-González et al . (2021) showed that TuMV-infected plants downregulate genes related with the formation of the secondary cell wall.…”
Section: Discussionsupporting
confidence: 94%
“…The copyright holder for this this version posted November 21, 2023. ; https://doi.org/10.1101/2023.11.21.568017 doi: bioRxiv preprint 9 ultimately, to the entire host via the phloem. In line with our results, López-González et al (2021) showed that TuMV-infected plants downregulate genes related with the formation of the secondary cell wall. They found that IRREGULAR XYLEM 9, a gene related with xylan synthesis (a key component of the secondary cell wall), was strongly downregulated upon TuMV infection.…”
Section: Transcriptomic Analyses Of Viral Adaptation Highlight Cell W...supporting
confidence: 91%